Remote Ischemic Preconditioning Prevents Acute Kidney Injury Following Coronary Angiography - Oladipupo Olafiranye, MD, MS; Adam C. Straub, PhD; Yingze Zhang, PhD; Rahul Chaudhary, MD, MBA; Megan P. Miller, BS; Kathan Trivedi, MD; Lawrence Hoang, MD; Oussama Khalifa, MD; Adetola Ladejobi, MD, MPH; Floyd W. Thoma, BS; Ning Feng, MD, PhD; Aref Rahman, MD; et al. (JACC: Advances)
Background: Patients undergoing invasive coronary angiography have an increased risk of acute kidney injury (AKI) for which there is no well-defined prophylactic therapy. Objectives: This study examined whether remote ischemic preconditioning (RIPC) reduces the rate of AKI in high-risk patients undergoing invasive coronary angiography. Methods: In this randomized sham-controlled trial, we enrolled high-risk patients undergoing coronary angiography between March 2018 and February 2023. Patients were randomly assigned 1:1 to RIPC or sham-RIPC. The primary outcome was the rate of AKI after coronary angiography. Secondary endpoints included changes in vascular and urinary biomarkers after RIPC, major adverse cardiovascular and cerebrovascular events (MACCE), and major adverse kidney events at 6-month follow-up. Results: A total of 109 patients (median age, 75 years) were randomized to RIPC (n = 54) and sham-RIPC (n = 55). The rate of AKI was lower in the RIPC compared to the sham-RIPC group (14.8% vs 29.1%; OR: 0.43; 95% CI: [0.17-0.94]; P = 0.030). The product of urinary tissue inhibitor of metalloproteinase-2 and insulin-like growth factor-binding protein-7, 2 markers of AKI, significantly increased at 48 hours post-angiography compared to pre-angiography level (0.51 vs 0.89; P = 0.004) in the sham-RIPC but not in the RIPC group (0.39 vs 0.68; P = 0.091). At 6-month follow-up, RIPC reduced the rate of MACCE (16.7% vs 36.4%; OR: 0.35; 95% CI: [0.14-0.87]; P = 0.029) but not major adverse kidney events (7.4% vs 10.4%; OR: 0.65; 95% CI: [0.17-2.46]; P = 0.740). Conclusions: In high-risk patients undergoing coronary angiography, RIPC reduced incidence of AKI and MACCE, and positively influenced biomarkers of kidney injury. (Biochemical Effects of Remote Ischemic Pre-Conditioning on Contrast-induced Acute Kidney Injury [BRICK]; NCT03236441)